2019
DOI: 10.1002/gepi.22262
|View full text |Cite
|
Sign up to set email alerts
|

Embracing study heterogeneity for finding genetic interactions in large‐scale research consortia

Abstract: Genetic interactions have been recognized as a potentially important contributor to the heritability of complex diseases. Nevertheless, due to small effect sizes and stringent multiple-testing correction, identifying genetic interactions in complex diseases is particularly challenging. To address the above challenges, many genomic research initiatives collaborate to form large-scale consortia and develop open access to enable sharing of genome-wide association study (GWAS) data. Despite the perceived benefits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Multiple studies employed NGS to reveal the epigenetic modifications in heart failure, including DNA methylation and histone (de-)acetylation, which provided insights and identification of the driving mechanism underlying the disease [ 5 , 6 ]. We previously showed the influence of histone acetylation changes on QRS complex-related GWAS loci in HCM [ 7 , 8 ]. Additionally, studies from our group and others have shown that H3K27ac corresponds to the gene expression in human cardiac tissues as well as human cardiomyocytes [ 9 , 10 ], highlighting it as a promising epigenetic mark for predicting gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies employed NGS to reveal the epigenetic modifications in heart failure, including DNA methylation and histone (de-)acetylation, which provided insights and identification of the driving mechanism underlying the disease [ 5 , 6 ]. We previously showed the influence of histone acetylation changes on QRS complex-related GWAS loci in HCM [ 7 , 8 ]. Additionally, studies from our group and others have shown that H3K27ac corresponds to the gene expression in human cardiac tissues as well as human cardiomyocytes [ 9 , 10 ], highlighting it as a promising epigenetic mark for predicting gene expression.…”
Section: Introductionmentioning
confidence: 99%